A four-component coupling reaction of carbon dioxide, amines, cyclic ethers and 3-triflyloxybenzynes for the synthesis of functionalized carbamates. Issue 46 (27th April 2018) - Xiong, Wenfang; Qi, Chaorong; Cheng, Ruixiang; Zhang, Hao; Wang, Lu; Yan, Donghao; Jiang, Huanfeng
Abstract : A novel four-component coupling reaction of carbon dioxide, amines, cyclic ethers and 3-triflyloxybenzynes for the synthesis of functionalized carbamates has been developed for the first time. Abstract : A novel four-component coupling reaction of carbon dioxide, amines, cyclic ethers and 3-triflyloxybenzynes has been developed for the first time, providing an efficient method for the synthesis of a series of functionalized carbamate derivatives in moderate to high yields. The process proceeds under mild, transition metal-free and fluoride-free conditions, leading to the formation of two new C–O bonds, one new C–N bond and one C–H bond in a single step.